The Impact of Banking Digital Transformation on Financial Performance With Firm Size as A Moderating Variable - Joana Rosie Shabatiny Degely; Eka Ananta Sidharta; Makaryanawati Makaryanawati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the impact of digital transformation on banking financial performance with firm size as a moderating variable. Banking financial performance in Indonesia shows a fluctuating trend with a decrease in Return on Assets (ROA) from 2.47% in 2019 to 1.59% in 2020, although experiencing an increase in 2022 to 2.01%. Digital transformation has become a strategic solution through reducing operational costs by up to 50-70%, creating new revenue streams, and increasing customer lifetime value. This study uses panel data from 29 banking companies listed on the Indonesia Stock Exchange for the period 2020-2024 with a total of 145 observations. The analytical method employed is Moderated Regression Analysis (MRA) with a Fixed Effects Model. The results show that digital transformation has a significant positive effect on financial performance (β = 0.0089; p = 0.029). Firm size is proven to moderate the relationship between digital transformation and financial performance positively and significantly (β = 0.0004; p = 0.047), indicating that larger banks obtain more optimal benefits from digital transformation compared to small and medium-sized banks. This study contributes theoretically to the Resource-Based View (RBV) in the context of digital transformation and provides practical implications for banking management in designing digitalization strategies tailored to firm size.